Understanding Frame on the Mindset of Orang Rimba Related to Pandemic Words - Diana Rozelin (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2022)
During the Covid-19 pandemic, some terms appear to represent the coronavirus. For some people, Covid-19 terms were familiar, but not for others, such as Orang Rimba (OR). Some terms were weird and new because it was pronounced in the English language, such as 'social distancing', 'rapid test', and 'lockdown'. Meanwhile, the role of the government, in this case, BKSDA was very important to stop the spread of this virus within the OR community. This article not only talked about language but also the implementation of health. The purposes of this research were: 1) to find out the government's role through BKSDA in educating OR about Covid-19 terms and its preventing actions; 2) to find out the perception of OR toward the words of Covid-19. This research was conducted qualitatively. The technique for collecting the data was observation, interview, documentation, and recording. Meanwhile, for analyzing the data used descriptive techniques. The results were: 1) BKSDA office visited each OR group and gave directions and examples on how to wash hands, wear masks, keep their distance, and keep the environment clean. The suitable methods in teaching new things to OR are exemplary and habituation. 2) from 15 vocabulary words related to the Covid-19 pandemic, OR knew only 5 words. It was a mask, virus, washing hands, hand sanitizer, and corona. The word mask, according to OR, was a fabric for covering the nose and mouth. The meaning of the virus and corona were evil animals. The word washing hand means besuh tangon/ cuci tangon.